Conference report on contractures in musculoskeletal and neurological conditions. Issue 6 (7th March 2020) - Nuckolls, Glen H.; Kinnett, Kathi; Dayanidhi, Sudarshan; Domenighetti, Andrea A.; Duong, Tina; Hathout, Yetrib; Lawlor, Michael W.; Lee, Sabrina S. M.; Magnusson, S. Peter; McDonald, Craig M.; McNally, Elizabeth M.; Miller, Natalie F.; et al.
Abstract: Limb contractures are debilitating complications associated with various muscle and nervous system disorders. This report summarizes presentations at a conference at the Shirley Ryan AbilityLab in Chicago, Illinois, on April 19–20, 2018, involving researchers and physicians from diverse disciplines who convened to discuss current clinical and preclinical understanding of contractures in Duchenne muscular dystrophy, stroke, cerebral palsy, and other conditions. Presenters described changes in muscle architecture, activation, extracellular matrix, satellite cells, and muscle fiber sarcomeric structure that accompany or predispose muscles to contracture. Participants identified ongoing and future research directions that may lead to understanding of the intersecting factors that trigger contractures. These include additional studies of changes in muscle, tendon, joint, and neuronal tissues during contracture development with imaging, molecular, and physiologic approaches. Participants identified the requirement for improved biomarkers and outcome measures to identify patients likely to develop contractures and to accurately measure efficacy of treatments currently available and under development.